Dimensionless parameters for the perforation of ductile plates by armor-piercing rounds. (October 2021) - Guo, Zherui; Chen, Weinong
Highlights: Scaling law for target plate perforation is reformulated in terms of two dimensionless parameters. Dimensionless parameters negate the need for additional empirical constants. Parameters can collapse ballistic perforation data via a simple linear relation. Nonlinear thickness effects can be explained without detracting from cavity expansion model. Parameters further show success for Ti-6Al-4V and steel plates impacted by various projectiles. Abstract: Two dimensionless parameters are proposed to predict the ballistic performance of aluminum alloy plates against armor-piercing projectiles. These dimensionless parameters allow for the prediction of ballistic-limit velocities without the need for separate empirical constants that are geometry-dependent. Predictions and data from different studies for several aluminum alloys against two APM2 calibers and one BS41 caliber show good agreement using the proposed parameters. We further explore the dimensionless parameters in terms of thicker targets to show that the nonlinearity at higher target thicknesses arise as a natural progression of the proposed parameters. These dimensionless parameters are extended to other similar ballistic experimental data for Ti-6Al-4V and show good predictive capabilities.